2014
DOI: 10.1155/2014/685072
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Workers and Standard Precautions: Perceptions and Determinants of Compliance in the Emergency and Trauma Triage of a Tertiary Care Hospital in South India

Abstract: Background. Careful adherence to standard precautions can protect both health care workers (HCWs) and patients from infections. The present study identified the perceptions and compliance with the use of standard precautions and assessed the determinants of noncompliance among the HCWs in an emergency and trauma triage centre. Methods. A cross-sectional study using a semistructured questionnaire was carried out to collect the relevant information from the study participants. Results. A total of 162 HCWs were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
29
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 16 publications
12
29
2
Order By: Relevance
“…Likewise, in comparison to the study from south India where about 28% of the respondents claimed using outer protective clothing when indicated and in developed countries where a whopping 62% consistently used these. 4,11 Doctors were better than nurses in almost all aspects of compliance including hand washing, as shown by other studies too. 12 Regarding eye protection, our study showed that none of the HCWs was compliant.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Likewise, in comparison to the study from south India where about 28% of the respondents claimed using outer protective clothing when indicated and in developed countries where a whopping 62% consistently used these. 4,11 Doctors were better than nurses in almost all aspects of compliance including hand washing, as shown by other studies too. 12 Regarding eye protection, our study showed that none of the HCWs was compliant.…”
Section: Discussionsupporting
confidence: 56%
“…These practices aim to both protect health care workers (HCWs) and prevent them from transmitting the infections to their patients. 4,5 Despite the availability of detailed guidelines, the awareness and practice of standard precautions vary among HCWs and have been found to be inadequate in both developed and developing countries. [6][7][8] Though many studies could be quoted regarding the practice of standard precautions among HCWs in various urban hospitals of India, there is lack of information about the same among HCWs functioning in peripheral health institution settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies show that compliance with standard precautions among nurses is still sub-optimal and inconsistent (Efstathiou, Papastavrou, Raftopoulos & Merkouris, 2011a;Gebresilassie, Kumei & Yemane, 2014;Punia, Nair & Shetty, 2014;Eljedi & Dalo, 2014;Jackson, Lowton & Griffiths, 2014;Takimani, 2015;Abu Bakar, Haruna, Teryila, Hamina & Ahmadu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, approximately three million HCWs experience percutaneous exposure to blood-borne pathogens each year. Various exposures can be prevented through careful compliance to universal precaution [7]. Nurses represent the largest percentage of the health care workers and they are the "core of the health care system".…”
Section: Introductionmentioning
confidence: 99%